Adjuvant chemotherapy of megestrol acetate in advanced breast cancer: A meta-analysis (Bangladesh Journal of Pharmacology, 2015)
To evaluate the effectiveness and safety of adjuvant chemotherapy of megestrol acetate (MA) in advanced breast cancer, we searched CBM, CNKI, VIP, Wangfang Data and PubMed, and collected randomized controlled trials (RCT) of adjuvant chemotherapy of MA in advanced breast cancer. MA significantly increased treatment efficiency (p=0.0010); improve weight (p